Listening to the "Extreme Poor": IGVGD participants speak on their success - Chowdhury, Nusrat S (Research and Evaluation Division, Brac, 2019)
Those dealing with the issues of poverty and development have recently acknowledged the heterogeneity of the poor. The extreme poor rest on the other side of this poverty spectrum. Women in the extreme poor households bear a larger burden of poverty than men do. The Income Generation for Vulnerable Groups Development (IGVGD) is a programme designed to link these destitute women from the poorest 10-15 percent of the population to mainstream development activities of BRAC. The aim of this paper is to locate the factors accountable for elevating the socioeconomic situation of some of these IGVGD participants. The discussion focuses on the lives of nine ex-VGD participants {those who have finished their 18- month food ration cycle/ with different involvement status and varying degrees of success. It appears that having male earning members in the household along with being inuolued in multiple income generating activities were important reasons for the success of these particular members. While searching for factors contributing to success, this study also encountered an existing discourse on the relationship between a woman's status, her idea of "honour," and her views on the changes due to programme intervention. This dialogue is suggestive of changes initiated by an exogenous source, such as the IGVGD programme, as well as their link with existing cultural ideals.